2019
DOI: 10.3389/fimmu.2019.00104
|View full text |Cite
|
Sign up to set email alerts
|

The Evolving Role of TRAFs in Mediating Inflammatory Responses

Abstract: TRAFs [tumor necrosis factor (TNF) receptor associated factors] are a family of signaling molecules that function downstream of multiple receptor signaling pathways and play a pivotal role in the biology of innate, and adaptive immune cells. Following receptor ligation, TRAFs generally function as adapter proteins to mediate the activation of intracellular signaling cascades. With the exception of TRAF1 that lacks a Ring domain, TRAFs have an E3 ubiquitin ligase activity which also contributes to their ability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
69
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(71 citation statements)
references
References 89 publications
2
69
0
Order By: Relevance
“…Elements upstream of p38 in c-di-AMP-triggered signaling module are still unknown. However, intracellular receptors of other PAMPs such as RIG-I or NOD1 are capable of activating p38 (28,(30)(31)(32). Also, recent reports indicate that the cyclic dinucleotides from pathogens can directly bind to the oxidoreductase RECON and modulate the inflammatory response (43).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elements upstream of p38 in c-di-AMP-triggered signaling module are still unknown. However, intracellular receptors of other PAMPs such as RIG-I or NOD1 are capable of activating p38 (28,(30)(31)(32). Also, recent reports indicate that the cyclic dinucleotides from pathogens can directly bind to the oxidoreductase RECON and modulate the inflammatory response (43).…”
Section: Discussionmentioning
confidence: 99%
“…Alternative models of activation of p38 have been reported, including intracellular activation. Molecules that can be recognized by cytoplasmic pattern recognition receptors such as RIG-I or NOD1 were shown to activate p38 (28)(29)(30)(31)(32).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we identified a TRAF3 homolog from L. vannamei (LvTRAF3) for the first time, explored its antiviral function and the relationship involving related immune pathways in shrimp. In mammals, TRAFs 1 through 6 share a conserved TRAF-C terminus, which is required for the hetero-and homo-oligomerization of TRAF proteins, and recruitment to TRAF binding motifs in the cytoplasmic domains of cell surface receptors, as well as certain cytoplasmic and nuclear proteins (1). LvTRAF3 also has a TRAF-C domain at its C terminus.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor necrosis factor receptor (TNFR)-associated factors (TRAFs) are intracellular signal transducers for a number of members of the immune receptor superfamily, which converge on inducing the production of proinflammatory factors, interferons (IFNs) and/or antimicrobial peptides (AMPs) (1). A total of six TRAF families, TRAF1-6, have been identified in mammals, most of which are implicated with several innate immune responses (1).…”
Section: Introductionmentioning
confidence: 99%
“…Specially, since TRAFs were discovered in TNF-R signaling, its role has been expanded to include involvement in more and more other inflammatory cytokine receptors, such as receptors for IL-2, IL-6, IL-1β, IL-17, IL-18, IL-33, type I IFNs, type III IFNs, M-CSF, GM-CSF, and C-type lectin receptors (Dhillon et al, 2019;Swaidani et al, 2019). Certainly, as intracellular scaffolding molecules, TRAFs play an indispensable role via the complex interactions with the inflammatory cytokine receptors in regulating pathophysiological processes in many human diseases, including autoimmune diseases, cancers, atherosclerosis, and type II diabetes, and they even have been recommended as suitable targets for therapeutic intervention (Choi et al, 2018;Nagashima et al, 2018;Zhu et al, 2018;Dhillon et al, 2019;Sajjad et al, 2019;Sangare et al, 2019). Meanwhile, the biological and functional roles of TRAFs in ischemia-reperfusion injury (IRI) of various organs have received much attention in recent years.…”
mentioning
confidence: 99%